Anode composition, anode for lithium secondary battery including the same, and lithium secondary battery including the anode

JP2025504038AActive Publication Date: 2025-02-06LG ENERGY SOLUTION LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024544989
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-22
Filing Date
2023-06-22
Publication Date
2025-02-06
Estimated Expiration
2043-06-22

AI Technical Summary

Benefits of technology

【0019】 本発明の一実施態様による負極組成物は、高容量の電池を製作するために、高容量素材であるシリコン系活物質を用いることにおいて、シリコン系活物質の体積膨脹による問題点を特定の負極バインダーを適用して解決したことを特徴とする。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504038000001_ABST
    Figure 2025504038000001_ABST
Patent Text Reader

Abstract

The present application relates to a negative electrode composition, a negative electrode for a lithium secondary battery including the same, and a lithium secondary battery including the negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0076784, filed with the Korean Intellectual Property Office on June 23, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to a negative electrode composition, a negative electrode for a lithium secondary battery including the same, and a lithium secondary battery including the negative electrode. [Background technology]

[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields in this area is the field of power generation and storage using electrochemical reactions.

[0004] At present, a representative example of an electrochemical element that uses such electrochemical energy is a secondary battery, and the range of its use is expanding more and more.

[0005] With the development of technology and increasing demand for mobile devices, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and widely used. In addition, research on methods for manufacturing high-density electrodes with higher energy density per unit volume as electrodes for such high-capacity lithium secondary batteries is being actively conducted.

[0006] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and removes lithium ions from the positive electrode, and silicon-based particles having a large discharge capacity can be used as the negative electrode active material.

[0007] In particular, in recent years, in response to the demand for high-density energy batteries, active research has been conducted into methods of increasing capacity by using silicon-based compounds such as Si / C and SiOx, which have a capacity 10 times larger than that of graphite-based materials, as negative electrode active materials. Silicon-based compounds, which are high-capacity materials, have a larger capacity than the conventionally used graphite, but they have the problem that their volume expands rapidly during charging, cutting off the conductive path and reducing the battery characteristics.

[0008] In order to solve the problems when using silicon-based compounds as negative electrode active materials, various methods have been discussed, such as a method of adjusting the driving potential, a method of additionally coating a thin film on the active material layer, a method of controlling the particle size of the silicon-based compound, and a method of suppressing the volume expansion itself, or a variety of methods of preventing the conductive path from being broken. However, in the case of the above methods, there is a possibility that the performance of the battery may be deteriorated, so there is a limit to the application, and there is still a limit to the commercialization of the manufacture of negative electrode batteries with a high content of silicon-based compounds.

[0009] In particular, research has been conducted on the composition of binders that change volume, and research has been conducted on the use of binder polymers that have strong lateral stress in order to suppress the volume expansion of negative electrode active materials, which have large volume changes due to charging and discharging. However, these binder polymers alone have limitations in suppressing the increase in electrode thickness due to the contraction and expansion of negative electrode active materials and the resulting deterioration in lithium secondary battery performance.

[0010] In order to solve the problem of the volume expansion of the negative electrode having the silicon-based active material, an aqueous binder having both dispersibility and adhesiveness is used. The aqueous binder has an advantage of improving dispersibility, but the volume expansion of the active material causes the breakage of electrical contact between the active materials due to cycles performed in a state of reduced elongation, resulting in a problem of reduced lifespan.

[0011] Furthermore, to improve the life characteristics, a rubber-based binder may also be used. However, in the case of silicon-based active materials, when only a rubber-based binder is used, it is known that this also has limitations because the rigidity of the binder is insufficient.

[0012] In addition, water-based binders have the problem of intensifying shrinkage due to heat when the electrodes are dried, which is a disadvantage in the process, but SBR rubber-based binders, which have excellent flexibility, have the difference that they tend to shrink less when dried.

[0013] Therefore, when using high-capacity materials to manufacture high-capacity batteries, research is needed into binders that do not break the conductive network due to the volume expansion of the active material and have excellent adhesive strength. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] Patent Publication No. 2009-080971 Summary of the Invention [Problem to be solved by the invention]

[0015] The present application relates to a binder that has excellent adhesive strength with a negative electrode current collector without breaking a conductive network due to volume expansion of a silicon-based active material in manufacturing a high-capacity and high-density negative electrode, and has confirmed through research that the above-mentioned problems can be solved by adjusting the Young's modulus and tensile strain value of the binder and adjusting the content. Therefore, the present application relates to a negative electrode composition, a negative electrode for a lithium secondary battery including the same, and a lithium secondary battery including the negative electrode. [Means for solving the problem]

[0016] One embodiment of the present specification is a negative electrode composition including a silicon-based active material; a negative electrode conductive material; and a negative electrode binder; wherein the negative electrode binder has a Young's modulus of 10 3 MPa or more, and a second binder having a tensile deformation rate (strain) of 15% or more, wherein the negative electrode binder satisfies the following formula 1: [Formula 1] 1≦X / Y<4 In the above formula 1, Y represents the part by weight of the first binder based on 100 parts by weight of the negative electrode binder; X means the part by weight of the second binder based on 100 parts by weight of the negative electrode binder.

[0017] In yet another embodiment, there is provided a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; and a negative electrode active material layer formed on one or both sides of the negative electrode current collector layer, the negative electrode active material layer comprising the negative electrode composition according to the present application.

[0018] Finally, there is provided a lithium secondary battery, comprising: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte. Effect of the Invention

[0019] The negative electrode composition according to one embodiment of the present invention is characterized in that, in order to manufacture a high-capacity battery using a silicon-based active material, which is a high-capacity material, a problem caused by volume expansion of the silicon-based active material is solved by applying a specific negative electrode binder.

[0020] In particular, the negative electrode binder has a Young's modulus of 10 3 MPa or more, and a second binder having a tensile deformation rate (strain) of 15% or more, and the negative electrode binder satisfies the range of specific formula 1.

[0021] Specifically, the negative electrode composition according to the present application improves dispersibility for dispersing active materials even when a silicon-based active material is used, and also contains a first binder and a second binder of specific compositions in order to improve adhesive strength, thereby solving the problems of conductive network disconnection due to adhesive strength and volume expansion in the initial and later stages of batteries using silicon-based active materials.

[0022] That is, the negative electrode composition according to the present application has a high content of silicon-based active material particles, thereby making it possible to obtain a high-capacity and high-density negative electrode, and in order to solve problems such as volume expansion caused by having a high content of silicon-based active material particles, a binder with a specific composition and content is used to solve the above problems, which is a main object of the present invention. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. [Diagram 2] FIG. 1 is a diagram showing a stacked structure of a lithium secondary battery according to an embodiment of the present application. [Diagram 3] FIG. 2 is a diagram showing a method for evaluating curl in the examples and comparative examples according to the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Before describing the present invention, some terms will first be defined. In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.

[0025] In this specification, "p to q" means "greater than or equal to p and less than or equal to q." In this specification, the "specific surface area" is measured by the BET method, and specifically, is calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-miniII manufactured by BEL Japan Co., Ltd. That is, in this application, the BET specific surface area can mean the specific surface area measured by the above-mentioned measurement method.

[0026] In this specification, "Dn" means particle size distribution, and refers to the particle size at n% of the cumulative particle number distribution by particle size. That is, D50 is the particle size (average particle size) at 50% of the cumulative particle number distribution by particle size, D90 is the particle size at 90% of the cumulative particle number distribution by particle size, and D10 is the particle size at 10% of the cumulative particle number distribution by particle size. Meanwhile, the particle size distribution may be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and when the particles pass through a laser beam, the difference in the diffraction pattern due to the particle size is measured to calculate the particle size distribution.

[0027] In the present specification, when a polymer contains a certain monomer as a monomer unit, it means that the monomer participates in a polymerization reaction and is contained as a repeating unit in the polymer. In the present specification, when a polymer contains a monomer, this is interpreted as the same as when a polymer contains a monomer as a monomer unit.

[0028] In this specification, the term "polymer" is understood to be used in a broad sense including copolymers, unless otherwise specified as a "homopolymer."

[0029] In this specification, the weight average molecular weight (Mw) and number average molecular weight (Mn) are polystyrene-equivalent molecular weights measured by gel permeation chromatography (GPC) using monodisperse polystyrene polymers (standard samples) of various degrees of polymerization commercially available for molecular weight measurement as standard substances. In this specification, the molecular weight means the weight average molecular weight unless otherwise specified.

[0030] In one embodiment of the present application, the Young's modulus is measured by putting the binder solution into a coated container and drying it at room temperature for a long time to remove moisture. The film from which the moisture has evaporated is vacuum dried at 130°C for 10 hours in accordance with the electrode drying temperature to obtain a dried film. The dried film is then cut or punched into a sample shape of 6 mm x 100 mm, and the tensile strength (Young's modulus) can be measured using UTM equipment.

[0031] The Young's modulus may vary depending on the measurement method, speed, and measurement condition of the binder, but the Young's modulus of the binder may be a value measured in a drying room with a dew point of -5°C to 10°C and a temperature of about 20°C to 22°C.

[0032] In this application, the dew point means the temperature at which condensation begins when humid air is cooled and the partial pressure of water vapor in the air becomes equal to the saturated vapor pressure of water at that temperature. In other words, it can mean the temperature at which dew begins to form when the temperature of a gas containing water vapor is lowered as it is, and the relative humidity becomes 100%.

[0033] The dew point of -5°C to 10°C and the temperature of about 20°C to 22°C can be defined as a normal dry room, and at this time, the humidity corresponds to a very low level.

[0034] In one embodiment of the present application, the method of measuring the tensile strain is to put the binder solution into a coated container, dry it at room temperature for a long time to remove moisture, and the film from which the moisture has evaporated is vacuum dried at 130°C for 10 hours according to the electrode drying temperature to obtain a dried film. The dried film is then cut or punched into a sample shape of 6mm x 100mm, and the tensile strain can be measured using UTM equipment.

[0035] The tensile deformation rate of the binder varies depending on the measurement method, speed, and measurement condition of the binder, but the tensile deformation rate (strain) of the binder is the same as the measurement condition of the Young's modulus.

[0036] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to the accompanying drawings in order to enable those skilled in the art to easily practice the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the disclosed embodiments.

[0037] One embodiment of the present specification is a negative electrode composition including a silicon-based active material; a negative electrode conductive material; and a negative electrode binder; wherein the negative electrode binder has a Young's modulus of 10 3 MPa or more, and a second binder having a tensile deformation rate (strain) of 15% or more, wherein the negative electrode binder satisfies the following formula 1:

[0038] [Formula 1] 1≦X / Y<4 In the above formula 1, Y represents the part by weight of the first binder based on 100 parts by weight of the negative electrode binder; X means the part by weight of the second binder based on 100 parts by weight of the negative electrode binder.

[0039] Specifically, the negative electrode composition according to the present application, even when using a silicon-based active material, improves the dispersibility for dispersing the active material, and also includes a first binder and a second binder having a specific composition to improve the adhesion, thereby solving the problems of adhesion in the initial and later stages of a battery using a silicon-based active material and disconnection of the conductive network due to volume expansion.

[0040] In one embodiment of the present application, the silicon-based active material may include one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), SiC, and Si alloy.

[0041] The active material of the present invention includes a silicon-based active material. The silicon-based active material may be SiOx, Si / C, or Si. SiOx may include a compound represented by SiOx (0 ≦ x < 2). In the case of SiO2, since it does not react with lithium ions and cannot store lithium, x is preferably within the above range. The silicon-based active material may be Si / C or Si composed of a composite of Si and C. Also, two or more of the above silicon-based active materials may be mixed and used. The negative electrode active material may further include a carbon-based active material together with the above silicon-based active material. The carbon-based active material can contribute to the improvement of the cycle characteristics or battery life performance of the negative electrode or secondary battery of the present invention.

[0042] Generally, it is known that a silicon-based active material has a capacity more than 10 times higher than that of a carbon-based active material. Thus, when applying a silicon-based active material to a negative electrode, it is expected that an electrode with a high level of energy density can be realized even with a thin thickness.

[0043] In one embodiment of the present application, a negative electrode composition is provided, wherein the silicon-based active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) is included in an amount of 70 parts by weight or more.

[0044] In another embodiment, the silicon-based active material may contain 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and may contain 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less of the SiOx (x = 0) based on 100 parts by weight of the silicon-based active material.

[0045] The silicon-based active material according to the present application contains 70 parts by weight or more of the SiOx (x = 0) based on 100 parts by weight of the silicon-based active material, and when compared with a silicon-based active material using a SiOx (0 < x < 2) series as the main substance, the theoretical capacity is much higher than that of the silicon-based active material of the present application. That is, when using an active material of the SiOx (0 < x < 2) series, no matter what treatment is performed on the active material itself, it is impossible to achieve conditions equivalent to the charge and discharge capacity compared to the case of having the silicon-based active material of the present invention.

[0046] In one embodiment of the present application, the silicon-based active material may use pure silicon (Si) as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material can mean, as described above, containing pure Si particles (SiOx (x = 0)) that are not bonded to other particles or elements within the above range based on 100 parts by weight of the entire silicon-based active material.

[0047] Compared with the conventionally used graphite-based active material, the silicon-based active material has a significantly higher capacity, and attempts to apply it are increasing. However, the volume expansion rate is high during the charge and discharge process, and it is only used by mixing a small amount with the graphite-based active material.

[0048] Therefore, in order to improve the capacity performance, the present invention is characterized by using a binder under specific conditions to solve the problems of maintaining the conductive path due to the above-mentioned volume expansion and maintaining the binding of the conductive material, binder, and active material while using a high content of the silicon-based active material as the negative electrode active material.

[0049] Meanwhile, the average particle size (D50) of the silicon-based active material of the present invention may be 5 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. When the average particle size is within the above range, the specific surface area of ​​the particles is within a suitable range, and the viscosity of the negative electrode slurry is formed within a suitable range. As a result, the particles constituting the negative electrode slurry are smoothly dispersed. In addition, when the size of the silicon-based active material is equal to or greater than the lower limit range, the contact area between the silicon particles and the conductive material is excellent due to the complex of the conductive material and the binder in the negative electrode slurry, and the conductive network is more likely to be maintained, thereby increasing the capacity retention rate. Meanwhile, when the average particle size satisfies the above range, silicon particles that are too large are excluded, and the surface of the negative electrode is formed smoothly, thereby preventing the phenomenon of non-uniform current density during charging and discharging.

[0050] In one embodiment of the present application, the silicon-based active material usually has a characteristic BET specific surface area. The BET specific surface area of ​​the silicon-based active material is preferably less than 0.01 m 2 / g~150.0m 2 / g, more preferably 0.1m 2 / g~100.0m 2 / g, particularly preferably 0.2m 2 / g~80.0m 2 / g, most preferably 0.2m 2 / g~18.0m 2 / g. The BET specific surface area is measured (using nitrogen) according to DIN 66131, which corresponds to a method for measuring porosity by the amount of adsorption / desorption of nitrogen molecules.

[0051] In one embodiment of the present application, the silicon-based active material may be present, for example, in crystalline or amorphous form, and is preferably not porous.The silicon particles are preferably spherical or multi-lobed particles.Alternatively, the silicon particles may have a fibrous structure or may be present in the form of a silicon-containing thin film or coating, but less preferably.

[0052] In one embodiment of the present application, there is provided a negative electrode composition, in which the silicon-based active material is 60 parts by weight or more based on 100 parts by weight of the negative electrode composition.

[0053] In another embodiment, the silicon-based active material may comprise 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, based on 100 parts by weight of the negative electrode composition, and may comprise 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 85 parts by weight or less.

[0054] The negative electrode composition according to the present application uses a specific conductive material and binder that can control the volume expansion rate during charging and discharging even when a silicon-based active material with a remarkably high capacity is used within the above range, and thus has the characteristic of excellent output characteristics during charging and discharging without deteriorating the performance of the negative electrode even when the above range is included.

[0055] In one embodiment of the present application, the silicon-based active material may have a non-spherical morphology, and the sphericity is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.

[0056] In this application, the circularity is determined by the following formula 1-1, where A is the area and P is the perimeter. [Formula 1-1] 4πA / P 2

[0057] In the past, it was common to use only graphite-based compounds as negative electrode active materials, but recently, as the demand for high-capacity batteries has increased, attempts to mix and use silicon-based compounds to increase capacity have been increasing. However, in the case of silicon-based compounds, even if the characteristics of the silicon-based active material itself are adjusted according to the present application as described above, the volume of the silicon-based compound may suddenly expand during charging / discharging, which may cause some problems in that the conductive path formed in the negative electrode active material layer is broken.

[0058] Therefore, in one embodiment of the present application, the negative electrode conductive material may include one or more selected from the group consisting of dot-like conductive materials, sheet-like conductive materials, and linear conductive materials.

[0059] In one embodiment of the present application, the dot-like conductive material refers to a dot-like or spherical conductive material that can be used to improve the conductivity of the negative electrode and has conductivity without inducing a chemical change. Specifically, the dot-like conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and preferably includes carbon black in terms of realizing high conductivity and excellent dispersibility.

[0060] In one embodiment of the present application, the point-like conductive material has a BET specific surface area of ​​40 m 2 / g or more and 70m 2 / g or less, preferably 45m 2 / g or more and 65m 2 / g or less, more preferably 50m 2 / g or more and 60m 2 / g or less.

[0061] In one embodiment of the present application, the point-like conductive material can satisfy a functional group content (volatile matter) of 0.01% or more and 1% or less, preferably 0.01% or more and 0.3% or less, and more preferably 0.01% or more and 0.1% or less.

[0062] In particular, when the functional group content of the dot-shaped conductive material satisfies the above range, the functional groups are present on the surface of the dot-shaped conductive material, and when water is used as a solvent, the dot-shaped conductive material can be smoothly dispersed in the solvent. In particular, by using silicon particles and a specific binder in the present invention, the functional group content of the dot-shaped conductive material can be reduced, thereby having an excellent effect in improving dispersibility.

[0063] In one embodiment of the present application, the active material is characterized in that it contains a dot-shaped conductive material having a functional group content in the above range together with a silicon-based active material, and the functional group content can be adjusted by the degree of heat treatment of the dot-shaped conductive material.

[0064] In one embodiment of the present application, the particle size of the dotted conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.

[0065] In one embodiment of the present application, the conductive material may include a sheet-shaped conductive material. The planar conductive material can increase surface contact between silicon particles in the negative electrode to improve conductivity, and at the same time, can suppress the disconnection of the conductive path due to volume expansion. The planar conductive material may be expressed as a planar conductive material, a plate-shaped conductive material, or a bulk-type conductive material.

[0066] In one embodiment of the present application, the sheet conductive material may include at least one selected from the group consisting of platelet graphite, graphene, graphene oxide, and graphite flakes, and may preferably be platelet graphite.

[0067] In one embodiment of the present application, the average particle size (D50) of the sheet conductive material may be 2 μm to 7 μm, specifically, 3 μm to 6 μm, and more specifically, 4 μm to 5 μm. If the above range is satisfied, the particle size is sufficient, so that the viscosity of the negative electrode slurry is not excessively increased, and dispersion is easy. Therefore, when dispersing using the same equipment and time, the dispersion effect is excellent.

[0068] In one embodiment of the present application, a negative electrode composition is provided in which the planar conductive material has a D10 of 0.5 μm or more and 2.0 μm or less, a D50 of 2.5 μm or more and 3.5 μm or less, and a D90 of 6.5 μm or more and 15.0 μm or less.

[0069] In one embodiment of the present application, the sheet conductive material may be a sheet conductive material having a high BET specific surface area; or a sheet conductive material having a low specific surface area.

[0070] In one embodiment of the present application, the sheet conductive material may be a sheet conductive material with a high specific surface area or a sheet conductive material with a low specific surface area without any restrictions. In particular, the sheet conductive material in the present application may be affected to some extent by the dispersion effect on the electrode performance, and it is particularly preferable to use a sheet conductive material with a low specific surface area in which dispersion problems do not occur.

[0071] In one embodiment of the present application, the sheet conductive material has a BET specific surface area of ​​1 m 2 / g or more.

[0072] In another embodiment, the sheet conductive material has a BET specific surface area of ​​1 m 2 / g or more and 500m 2 / g or less, preferably 5m 2 / g or more and 300m 2 / g or less, more preferably 5m 2 / g or more and 250m 2 / g.

[0073] The sheet conductive material according to the present application may be a sheet conductive material with a high specific surface area; or a sheet conductive material with a low specific surface area.

[0074] In another embodiment, the sheet conductive material is a sheet conductive material having a high specific surface area and a BET specific surface area of ​​50 m 2 / g or more and 500m 2 / g or less, preferably 80m 2 / g or more and 300m 2 / g or less, more preferably 100m 2 / g or more and 300m 2 / g or less range can be satisfied.

[0075] In another embodiment, the sheet conductive material is a sheet conductive material having a low specific surface area and a BET specific surface area of ​​1 m 2 / g or more and 40m 2 / g or less, preferably 5m 2 / g or more and 30m 2 / g or less, more preferably 5m 2 / g or more and 25m 2 / g or less range can be satisfied.

[0076] Alternatively, the conductive material may be a linear conductive material such as a carbon nanotube. The carbon nanotube may be a bundle-type carbon nanotube. The bundle-type carbon nanotube may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle type" refers to a secondary shape in which a plurality of carbon nanotube units are arranged in parallel with the longitudinal axis of the carbon nanotube units being substantially aligned in the same direction or twisted into a bundle or rope. The carbon nanotube unit has a graphite sheet having a nano-sized cylindrical shape and an sp2 bond structure. In this case, the graphite sheet may exhibit conductive or semiconductive properties depending on the angle and structure at which it is wound. The bundle-type carbon nanotube may be uniformly dispersed during the manufacture of the negative electrode compared to an entangled type carbon nanotube, and may smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.

[0077] In one embodiment of the present application, the negative electrode composition is provided in which the negative electrode conductive material is 0.1 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode composition. Also, for example, the negative electrode conductive material may include 10 parts by weight or more and 40 parts by weight or less.

[0078] In yet another embodiment, the negative electrode conductive material may comprise, based on 100 parts by weight of the negative electrode composition, 0.1 parts by weight or more and 40 parts by weight or less, preferably 0.2 parts by weight or more and 30 parts by weight or less, more preferably 0.4 parts by weight or more and 25 parts by weight or less, and most preferably 0.4 parts by weight or more and 10 parts by weight or less.

[0079] In one embodiment of the present application, there is provided a negative electrode composition, wherein the negative electrode conductive material includes a planar conductive material and a linear conductive material.

[0080] In one embodiment of the present application, a negative electrode composition is provided in which the negative electrode conductive material includes, based on 100 parts by weight of the negative electrode conductive material, 80 parts by weight or more and 99.9 parts by weight or less of the sheet conductive material; and 0.1 parts by weight or more and 20 parts by weight or less of the linear conductive material.

[0081] In another embodiment, the negative electrode conductive material may contain 80 parts by weight or more and 99.9 parts by weight or less, preferably 85 parts by weight or more and 99.9 parts by weight or less, and more preferably 95 parts by weight or more and 98 parts by weight or less, of the sheet conductive material, based on 100 parts by weight of the negative electrode conductive material.

[0082] In another embodiment, the negative electrode conductive material may contain 0.1 parts by weight or more and 20 parts by weight or less, preferably 0.1 parts by weight or more and 15 parts by weight or less, and more preferably 0.2 parts by weight or more and 5 parts by weight or less of the linear conductive material, based on 100 parts by weight of the negative electrode conductive material.

[0083] In one embodiment of the present application, the negative electrode conductive material includes a sheet conductive material and a linear conductive material, each of which satisfies the above-mentioned composition and ratio, so that the life characteristics of conventional lithium secondary batteries are not significantly affected. In particular, when the negative electrode conductive material includes a sheet conductive material and a linear conductive material, the number of points at which charging and discharging are possible increases, resulting in excellent output characteristics at a high C-rate and a reduced amount of gas generation at high temperatures.

[0084] In one embodiment of the present application, the negative electrode conductive material may be made of a linear conductive material. In particular, when the linear conductive material is used alone, the tortuosity of the electrode, which is a problem with silicon-based negative electrodes, can be simplified and the electrode structure can be improved, thereby reducing the resistance to lithium ion migration within the electrode.

[0085] In one embodiment of the present application, when the negative electrode conductive material contains only a linear conductive material, the negative electrode conductive material may contain 0.1 parts by weight or more and 5 parts by weight or less, preferably 0.2 parts by weight or more and 3 parts by weight or less, and more preferably 0.4 parts by weight or more and 1 part by weight or less, based on 100 parts by weight of the negative electrode composition.

[0086] The negative electrode conductive material according to the present application has a completely different structure from the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application plays a role of controlling the contact between the silicon-based active material, which has a very large volume expansion of the electrode due to charging and discharging, and the positive electrode conductive material plays a role of providing some conductivity while acting as a buffer when rolled, and has a completely different structure and role from the negative electrode conductive material of the present invention.

[0087] In addition, the negative electrode conductive material according to the present application is applied to a silicon-based active material, and has a completely different structure from a conductive material applied to a graphite-based active material. That is, a conductive material used in an electrode having a graphite-based active material has particles that are simply smaller than the active material, and therefore has the properties of improving output characteristics and imparting some electrical conductivity, and has a completely different structure and role from a negative electrode conductive material applied together with a silicon-based active material as in the present invention.

[0088] In one embodiment of the present application, the planar conductive material used as the negative electrode conductive material has a structure and role different from that of the carbon-based active material usually used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and means a material that is processed into a spherical or dot-like shape to facilitate the storage and release of lithium ions.

[0089] Meanwhile, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, which may be expressed as plate-like graphite. That is, it is a material contained in the negative electrode active material layer to maintain a conductive path, and does not function to store and release lithium, but rather to ensure a planar conductive path inside the negative electrode active material layer.

[0090] That is, in the present application, the use of plate-shaped graphite as a conductive material means that it is processed into a planar or plate-shaped form and used as a material to ensure a conductive path rather than to store or release lithium. In this case, the negative electrode active material contained therein has high capacity characteristics for storing and releasing lithium, and plays a role in storing and releasing all the lithium ions transferred from the positive electrode.

[0091] Meanwhile, in the present application, the carbon-based active material being used as an active material means that it is processed into a dotted or spherical shape and used as a material that plays a role in storing or releasing lithium.

[0092] In one embodiment of the present application, the negative electrode binder has a Young's modulus of 10 3 MPa or more, and a second binder having a tensile deformation rate (strain) of 15% or more.

[0093] In one embodiment of the present application, there is provided a negative electrode composition, wherein the first binder comprises one or more selected from the group consisting of PAA, PAN, and PAM, and the second binder is a rubber-based binder.

[0094] In one embodiment of the present application, the negative electrode binder has a Young's modulus of 10 3 MPa or more.

[0095] In another embodiment, the negative electrode binder has a Young's modulus of 1×10 3 MPa or more, preferably 2×10 3 MPa, more preferably 5×10 3 MPa or more, most preferably 9×10 3 MPa or more, and may be 20×10 3 MPa or less, preferably 18×10 3 MPa or less, more preferably 15×10 3 MPa or less.

[0096] In another embodiment, the Young's modulus of the negative electrode binder is 3×10 3 MPa or more, 4×10 3 MPa or more, 6×10 3 MPa or more, 7×10 3 MPa or more, 8×10 3 MPa or more, 10 x 10 3 MPa or more, 19×10 3 MPa or less, 17×10 3 MPa or less, 16×10 3 MPa or less, 14×10 3 MPa or less, 13×10 3 MPa or less, 12×10 3MPa or less, including all of the various combinations of ranges recited above.

[0097] The first binder has dispersibility for dispersing the negative electrode active material in a negative electrode slurry state containing the negative electrode composition, and adhesive strength for binding with the negative electrode current collector layer and the negative electrode active material layer after drying, and corresponds to a binder whose adhesive strength is not high. That is, the first binder according to the present application may mean a binder having a surface-adhesive form, including an aqueous binder satisfying the Young's modulus.

[0098] The first binder is a binder suitable for a lithium secondary battery in which a silicon active material that exhibits large volume expansion during charging and discharging is applied to a negative electrode. If the first binder is below the lower limit of the range, it is difficult to effectively control the volume expansion of silicon, and if the first binder is above the upper limit of the range, the rigidity is too high and the binder is likely to crack during charging and discharging.

[0099] In one embodiment of the present application, the aqueous binder is one that can be dissolved in an aqueous solvent such as water, and includes at least one selected from the group consisting of polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyethylene glycol (PEG), polyacrylonitrile (PAN), and polyacrylamide (PAM). Preferably, in terms of having excellent resistance to volume expansion / contraction of the silicon-based active material, the aqueous binder may include at least one selected from the group consisting of polyacrylic acid (PAA) and polyacrylamide (PAM), more preferably polyacrylic acid (PAA) and polyacrylamide (PAM).

[0100] More specifically, the first binder may be a PAM-based binder. In this case, the PAM-based binder is a binder mainly composed of PAM, and the ratio of PAM, PAA, and PAN may be adjusted, and the composition may be appropriately changed to satisfy the Young's modulus.

[0101] The first binder may include a binder in which hydrogen in the first binder is substituted with Li, Na, Ca, or the like in order to allow the first binder to be better dispersed in an aqueous solvent such as water and to more smoothly coat the active material and improve binding strength when preparing a negative electrode slurry for forming a negative electrode active material layer.

[0102] The first binder is hydrophilic and does not dissolve in electrolytes or electrolytic solutions typically used in secondary batteries. Such characteristics can impart strong stress or tensile strength to the first binder when applied to a negative electrode or lithium secondary battery, thereby effectively suppressing the volume expansion / contraction problem of silicon-based active materials due to charge / discharge.

[0103] In one embodiment of the present application, there is provided a negative electrode composition, wherein the weight average molecular weight of the first binder is 100,000 g / mol or more and 2,000,000 g / mol or less.

[0104] More preferably, it may be 500,000 g / mol or more and 1,500,000 g / mol or less.

[0105] In one embodiment of the present application, the second binder may have a tensile strain of 15% or more, preferably a tensile strain of 20% or more, more preferably a tensile strain of 30% or more, and most preferably a tensile strain of 40% or more, and may have a tensile strain of 300% or less, preferably 200% or less, and more preferably 150% or less.

[0106] In another embodiment, the tensile strain may be 25% or more, 35% or more, 45% or more, 75% or less, 65% or less, or 55% or less, and various combinations of these ranges may be included.

[0107] As described above, if the tensile strain value of the second binder is below the above range, the stress is high and it is difficult to effectively control the volume expansion of silicon, and if it exceeds the above range, it is difficult to effectively control the adhesive force between the electrodes.

[0108] Since the first binder has a strong stress by satisfying the above modulus range, there is a risk of bending of the negative electrode, cracking due to bending, and deterioration of life characteristics when the first binder is used alone. The second binder can be easily dissolved in an electrolyte or electrolytic solution generally used in secondary batteries, and can be used together with the first binder to reduce the stress of the first binder to a certain level.

[0109] Therefore, the negative electrode composition of the present invention has the following characteristics: by using an anode binder containing the first binder and the second binder in a specific weight ratio, the problem of volume expansion / contraction of a silicon-based active material can be effectively solved, and life characteristics can be improved; during the manufacture of a thin film anode, bending problems can be solved, and adhesive strength can be improved.

[0110] In this case, the tensile strain value of the second binder can be realized within the above range by adjusting the ST / BD ratio of the SBR binder within an appropriate range.

[0111] In one embodiment of the present application, the second binder may be defined as a material different from the first binder, which is not easily dissolved in an aqueous solvent such as water, but can be smoothly dispersed in an aqueous solvent. Specifically, the second binder having a tensile strain of 15% or more may include at least one selected from the group consisting of styrene butadiene rubber (SBR), hydrogenated nitrile butadiene rubber (HNBR), acrylonitrile butadiene rubber, acrylic rubber, butyl rubber, and fluoro rubber, and preferably includes at least one selected from the group consisting of styrene butadiene rubber and hydrogenated nitrile butadiene rubber, more preferably styrene butadiene rubber, in terms of easy dispersion and excellent phase stability.

[0112] In general, the second binder is a material that has a higher wettability with the electrolyte than the first binder. When the second binder is located near the surface of the silicon-based negative electrode, the FEC solvent and LiPF6 salt that can form the SEI layer can be supplied quickly, resulting in a lower negative electrode resistance.

[0113] In one embodiment of the present application, the formula 1 may satisfy 1≦X / Y<4, preferably 1.1≦X / Y<3.9, and more preferably 1.2≦X / Y<3.8.

[0114] More specifically, it may be 1.3≦X / Y<3.7, 1.4≦X / Y<3.6, 1.5≦X / Y<3.5, 1.6≦X / Y<3.4, ​​1.7≦X / Y<3.3, 1.8≦X / Y<3.2, 1.9≦X / Y<3.1, 2.0≦X / Y<3.0, or 1.2≦X / Y<2.0.

[0115] In one embodiment of the present application, X is 50 parts by weight or more and 95 parts by weight or less based on 100 parts by weight of the negative electrode binder, and Y is 5 parts by weight or more and 50 parts by weight or less based on 100 parts by weight of the negative electrode binder.

[0116] In another embodiment, X may be 50 parts by weight or more and 95 parts by weight or less, preferably 55 parts by weight or more and 90 parts by weight or less, more preferably 55 parts by weight or more and 80 parts by weight or less, based on 100 parts by weight of the negative electrode binder. It may also be 50 parts by weight or more and 70 parts by weight or less, 55 parts by weight or more and 67 parts by weight or less, or 60 parts by weight or more and 67 parts by weight or less.

[0117] In another embodiment, the Y may be 5 parts by weight or more and 50 parts by weight or less, preferably 10 parts by weight or more and 45 parts by weight or less, more preferably 20 parts by weight or more and 45 parts by weight or less, based on 100 parts by weight of the negative electrode binder, or may be 33 parts by weight or more and 45 parts by weight or less, 35 parts by weight or more and 45 parts by weight or less, or 40 parts by weight or more and 45 parts by weight or less.

[0118] As described above, the negative electrode binder according to the present application has the characteristics that the first binder and the second binder satisfy the above-mentioned contents, and thus improves dispersibility and solves the problem of adhesive strength even when a silicon-based active material is used.

[0119] Since the first binder has a strong stress by satisfying the above modulus range, when only the first binder is used alone, there is a risk of bending of the negative electrode, cracking due to bending, and deterioration of life characteristics. The second binder can be easily dissolved in an electrolyte or electrolytic solution generally used in secondary batteries, and can be used together with the first binder to reduce the stress of the first binder to a certain level.

[0120] Therefore, the negative electrode composition of the present invention has the following characteristics: by using the negative electrode binder containing the first binder and the second binder in a specific weight ratio, the volume expansion / contraction problem of the silicon-based active material can be effectively solved, the bending problem during the manufacture of the thin film negative electrode can be solved, and the adhesive strength can be improved.

[0121] Furthermore, when the negative electrode binder and the negative electrode conductive material contain a sheet conductive material and a linear conductive material, the adhesive strength problem can be improved and the negative electrode internal resistance can also be improved.

[0122] In one embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.

[0123] In one embodiment of the present application, a negative electrode composition is provided in which the negative electrode binder is 1 part by weight or more and 20 parts by weight or less, based on 100 parts by weight of the negative electrode composition.

[0124] In one embodiment of the present application, the negative electrode binder may be included in an amount of 20 parts by weight or less, preferably 15 parts by weight or less, based on 100 parts by weight of the negative electrode composition, and may be included in an amount of 1 part by weight or more, 5 parts by weight or more, or 10 parts by weight or more.

[0125] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; and a negative electrode active material layer formed on one or both sides of the negative electrode current collector layer, the negative electrode active material layer comprising the negative electrode composition according to the present application.

[0126] 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. Specifically, a negative electrode for a lithium secondary battery 100 including a negative electrode active material layer 20 on one side of a negative electrode current collector layer 10 can be seen. Although FIG. 1 shows that the negative electrode active material layer is formed on one side, it may be formed on both sides of the negative electrode current collector layer.

[0127] In one embodiment of the present application, the negative electrode may be formed by coating one or both sides of a current collector with a negative electrode slurry including the negative electrode composition to form a negative electrode for a lithium secondary battery.

[0128] In one embodiment of the present application, the negative electrode slurry may include a negative electrode composition; and a slurry solvent.

[0129] In one embodiment of the present application, the solid content of the negative electrode slurry may be 5% or more and 40% or less.

[0130] In another embodiment, the solid content of the negative electrode slurry may satisfy the range of 5% or more and 40% or less, preferably 7% or more and 35% or less, and more preferably 10% or more and 30% or less.

[0131] The solid content of the negative electrode slurry may refer to the content of the negative electrode composition contained in the negative electrode slurry, or may refer to the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.

[0132] When the solid content of the negative electrode slurry satisfies the above range, the viscosity is appropriate during the formation of the negative electrode active material layer, and the caking phenomenon of particles of the negative electrode composition is minimized, thereby enabling the negative electrode active material layer to be efficiently formed.

[0133] In one embodiment of the present application, the negative electrode current collector layer usually has a thickness of 1 μm to 100 μm. Such a negative electrode current collector layer is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, plastic carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy may be used. In addition, fine irregularities may be formed on the surface to strengthen the binding force of the negative electrode active material, and it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0134] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and the negative electrode active material layer has a thickness of 20 μm or more and 500 μm or less.

[0135] However, the thickness may vary depending on the type and application of the negative electrode used, and is not limited thereto.

[0136] In one embodiment of the present application, the porosity of the negative electrode active material layer can satisfy the range of 10% or more and 60% or less.

[0137] In another embodiment, the porosity of the negative electrode active material layer can satisfy the range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.

[0138] The porosity varies depending on the composition and content of the silicon-based active material, conductive material, and binder contained in the negative electrode active material layer, and in particular, the silicon-based active material and conductive material according to the present application are contained in specific compositions and content portions to satisfy the above range, thereby providing an electrode with appropriate ranges of electrical conductivity and resistance.

[0139] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, in which the adhesive strength of a surface of the negative electrode active material layer in contact with the negative electrode current collector layer satisfies 100 gf / 5 mm or more and 500 gf / 5 mm or less under conditions of 25° C. and normal pressure.

[0140] In still another embodiment, the adhesive strength of the surface of the negative electrode active material layer in contact with the negative electrode current collector layer may be 100 gf / 5 mm or more and 500 gf / 5 mm or less, preferably 300 gf / 5 mm or more and 450 gf / 5 mm or less, and more preferably 350 gf / 5 mm or more and 430 gf / 5 mm or less, under conditions of 25° C. and normal pressure.

[0141] In particular, the negative electrode according to the present application includes a specific negative electrode binder in the negative electrode composition, thereby improving adhesion as described above. In addition, even if the silicon-based active material expands and contracts repeatedly due to repeated charging and discharging of the negative electrode, the negative electrode binder and negative electrode conductive material of a specific composition are applied to maintain the conductive network, prevent disconnection, and suppress an increase in resistance.

[0142] The adhesive strength was measured at 90° and a speed of 5 mm / s using a peel strength tester with 3M 9070 tape. Specifically, one side of the negative electrode active material layer of the negative electrode for the lithium secondary battery was attached to one side of a slide glass (3M 9070 tape) with an adhesive film. Then, a 2 kg rubber roller was rolled back and forth 5 to 10 times to adhere the layer, and the adhesive strength (peel strength) was measured at an angle of 90° and a speed of 5 mm / s. The adhesive strength can be measured at 25°C and normal pressure.

[0143] Specifically, the adhesive strength was measured on a 5 mm x 15 cm electrode at 25°C and normal pressure.

[0144] In one embodiment of the present application, normal pressure may mean pressure without adding or reducing a specific pressure, and may be used in the same sense as atmospheric pressure. Usually, it may be expressed as 1 atmosphere.

[0145] In one embodiment of the present application, there is provided a lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.

[0146] 2 is a diagram showing a laminated structure of a lithium secondary battery according to an embodiment of the present application. Specifically, a lithium secondary battery anode 100 including an anode active material layer 20 on one side of an anode current collector layer 10 can be seen, and a lithium secondary battery cathode 200 including a cathode active material layer 40 on one side of a cathode current collector layer 50 can be seen, and the lithium secondary battery anode 100 and the lithium secondary battery cathode 200 are laminated with a separator 30 sandwiched therebetween.

[0147] A secondary battery according to an embodiment of the present specification may include the negative electrode for a lithium secondary battery described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.

[0148] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.

[0149] In the positive electrode, the positive electrode current collector is not particularly limited as long as it is conductive and does not induce chemical changes in the battery, and may be, for example, stainless steel, aluminum, nickel, titanium, plastic carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0150] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 Ni-site type lithium nickel oxide represented by the chemical formula LiMn 2-c3 M c3 Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M can be at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be metallic lithium (Li-metal).

[0151] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material described above.

[0152] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.

[0153] In addition, the positive electrode binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector.Specific examples include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination.

[0154] The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator that is generally used in secondary batteries may be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent humidification ability of the electrolyte solution is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, a coated separator containing a ceramic component or a polymeric material to ensure heat resistance or mechanical strength may be used, and may be selectively used in a single layer or multilayer structure.

[0155] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these. Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0156] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0157] In particular, among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, are highly viscous organic solvents having a high dielectric constant and capable of dissociating lithium salts, and therefore can be preferably used. When such a cyclic carbonate is mixed with a chain carbonate having a low viscosity and a low dielectric constant, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and therefore such a cyclic carbonate can be more preferably used.

[0158] The metal salt may be a lithium salt, and the lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte solution. For example, the anion of the lithium salt is F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 -, CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more selected from the group consisting of may be used.

[0159] In addition to the constituents of the electrolyte, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in the capacity of the battery, and improving the discharge capacity of the battery.

[0160] According to an embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the battery module. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and therefore may be used as a power source for a medium- to large-sized device selected from the group consisting of an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, and a power storage system.

[0161] In one embodiment of the present application, a method for manufacturing a negative electrode using the negative electrode composition is provided. More specifically, a solvent is added to the negative electrode composition to obtain a negative electrode slurry. The negative electrode slurry is applied to at least one surface of a negative electrode current collector layer to form a negative electrode active material layer. Thereafter, the negative electrode active material layer coated on the negative electrode current collector layer is dried and rolled to manufacture a negative electrode.

[0162] In the present application, the solvent contained in the negative electrode slurry may be, for example, distilled water. In one embodiment of the present application, the negative electrode slurry may have a solid content of 5% or more and 40% or less.

[0163] In another embodiment, the negative electrode slurry may have a solids content range of 5% to 40%, preferably 7% to 35%, and more preferably 10% to 30%.

[0164] The solid content of the negative electrode slurry may refer to the amount of the negative electrode composition contained in the negative electrode slurry, or may refer to the amount of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.

[0165] When the negative electrode slurry satisfies the solid content range of 5% to 40%, the negative electrode active material layer has an appropriate viscosity when formed, and thus the particle agglomeration phenomenon of the negative electrode active material is minimized in the electrode composition, thereby allowing the negative electrode active material layer to be efficiently formed.

[0166] Below, preferred embodiments are presented to aid in understanding the present invention. However, these embodiments are merely illustrative of the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present description. Naturally, such changes and modifications fall within the scope of the claims. EXAMPLES

[0167] <Production of negative electrode composition> Negative electrode compositions having the compositions and contents shown in Table 1 below were prepared.

[0168] [Table 1]

[0169] In Table 1, the silicon-based active material is Si (average particle size (D50): 5 μm), and the plate-shaped conductive material A has a BET specific surface area of ​​17 m 2 / g, D10: 1.7 μm, D50: 3.5 μm, D90: 6.8 μm, and the SWCNTs have a BET specific surface area of ​​1000 m 2 / g~1500m 2 / g and an aspect ratio of 10,000 or more were used.

[0170] In addition, in Table 1, the first binder, PAM-1, has a Young's modulus of 15×10 3 MPa (=15GPa), and PAM-2 has a Young's modulus of 9×10 3 MPa (9GPa), and PAN has a Young's modulus of 10 2 MPa.

[0171] In addition, in Table 1, as the second binder, SBR-1 is a binder with a tensile deformation rate (strain) of 60%, SBR-2 is a binder with a tensile deformation rate (strain) of 40%, and SBR-3 is a binder with a tensile deformation rate (strain) of 10%.

[0172] In this case, the Young's modulus of the first binder is a binder having PAM as a main component, and is adjusted by adjusting the mixing ratio of PAA and PAN to satisfy the above range, and the tensile deformation rate (Strain) value of the second binder is an SBR binder, and is adjusted by adjusting the ST / BD ratio to satisfy the above range.

[0173] The weight average molecular weight of the first binder is 5.0×10 5~1.5×10 6 Although the weight average molecular weight of the second binder before cross-linking can be measured, the weight average molecular weight is not measured since the second binder is in the form of spherical particles in practical use.

[0174] In Table 1, the content may refer to the weight ratio (parts by weight) of each component based on 100 parts by weight of the total negative electrode composition.

[0175] Anode production The negative electrode composition having the composition shown in Table 1 was added to distilled water as a solvent for forming a negative electrode slurry to prepare a negative electrode slurry (solid concentration: 25 wt %).

[0176] Then, the negative electrode was applied with a thickness of 76.34 mg / 25 cm on a 38 μm thick copper foil (Cu foil) with a thickness of 8 μm. 2 After coating the negative electrode active material layer, the negative electrode was dried at 130° C. for 12 hours and rolled to a porosity of 40% to prepare a negative electrode.

[0177] <Secondary battery manufacturing> As the positive electrode active material, LiNi 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added in a weight ratio of 97:1.5:1.5 to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry to prepare a positive electrode slurry (solid concentration 78 wt%).

[0178] The positive electrode current collector was an aluminum current collector (thickness: 12 μm) on both sides of which the positive electrode slurry was applied at 537 mg / 25 cm. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer (thickness: 65 μm) to prepare a positive electrode (thickness of positive electrode: 77 μm, porosity: 26%).

[0179] A polyethylene separator was interposed between the positive electrode and the negative electrode of Example 1 and Comparative Example, and an electrolyte was injected to prepare a lithium secondary battery.

[0180] The electrolyte was prepared by adding 3% by weight of vinylene carbonate (based on the total weight of the electrolyte) to an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) were mixed in a volume ratio of 10:90, and LiPF6 was added as a lithium salt at a concentration of 1M.

[0181] Mono cells were fabricated in the same manner as described above, except that the negative electrodes of the Examples and Comparative Examples were used, and life characteristics were evaluated in the range of 4.2-3.0V.

[0182] Experimental example 1: Evaluation of mono cell life characteristics at room temperature (25℃, 4.2-3.0V) The secondary batteries including the negative electrodes prepared in the Examples and Comparative Examples were subjected to a life evaluation using an electrochemical charger / discharger to evaluate the capacity retention rate. The secondary batteries were subjected to a cycle test at 4.2-3.0V, 1C / 0.5C, and the number of cycles at which the capacity retention rate reached 80% was measured. Capacity retention rate (%) = {(discharge capacity at Nth cycle) / (discharge capacity at first cycle)} x 100 The results are shown in Table 2 below.

[0183] Experimental example 2: Measurement and evaluation of mono-cell resistance increase rate (250 cycles, @SOC50, discharge) In the test in Experimental Example 1, the capacity retention rate was measured by charging / discharging at 0.33C / 0.33C (4.2-3.0V) every 50 cycles, and then the resistance was measured by discharging at 2.5C pulse at SOC50, and the resistance increase rate was compared and analyzed. For the resistance increase rate measurement evaluation, data at 250 cycles was calculated, and the results are shown in Table 2 below.

[0184] Experimental example 3: Evaluation of high temperature life characteristics of mono cell (45℃, 4.2-3.0V) The secondary batteries including the negative electrodes prepared in the Examples and Comparative Examples were subjected to a life evaluation using an electrochemical charger / discharger to evaluate the capacity retention rate. The secondary batteries were subjected to a cycle test at 4.2-3.0V, 1C / 0.5C, and the number of cycles at which the capacity retention rate reached 80% was measured. The results are shown in Table 2 below.

[0185] Experimental example 4: Electrode curl measurement The bending strength was measured by measuring the height of the center after the coated electrode was placed with the coating facing up as shown in Figure 3. That is, when the binder dries, tensile force acts on the coating, causing it to dent, which causes curling. The degree of curling was measured, and the results are shown in Table 2 below.

[0186] [Table 2]

[0187] As in Examples 1 to 6, it was confirmed that the first binder and the second binder are included, and SBR satisfying specific formula 1 and having a certain range of tensile strain is blended, so that the contact points between the active materials can be maintained even when the volume expands due to the progress of cycles, and the resistance increase rate is low, and therefore the life performance at room temperature and high temperature is also excellent.

[0188] For reference, when comparing Examples 1, 3, and 4 with Comparative Examples 1, 4, and 5, it was confirmed that the higher the SBR ratio, the less the electrode curl occurs, which is advantageous for process stability. However, as in the case of Comparative Example 4, when the SBR ratio is less than the ratio of the present application, it was confirmed that the curl phenomenon becomes serious.

[0189] For reference, Comparative Example 1 is a case where the second binder is not included, Comparative Example 2 is a case where the first binder is not included, Comparative Example 3 is a case where the first binder and the second binder are included but the content range exceeds the range of formula 1, Comparative Example 4 is a case where the content range is below the range of formula 1, Comparative Example 5 corresponds to a case where the range of formula 1 is satisfied but the Young's modulus of the first binder is below the range of the present application, and Comparative Example 6 corresponds to a case where the range of formula 1 is satisfied but the tensile deformation rate (strain) of the second binder is below the range of the present application.

[0190] When the comparative examples 1 to 6 were examined, it was confirmed that the life characteristics were lower and the resistance increase rate was higher than those of the examples 1 to 6 of the present application, and that the curl phenomenon also occurred frequently.

[0191] That is, it has been confirmed that the negative electrode composition according to the present application improves dispersibility for dispersing active materials even when a silicon-based active material is used, and contains a first binder and a second binder of specific compositions in order to improve adhesive strength, thereby solving the problems of conductive network disconnection due to adhesive strength and volume expansion in the initial and later stages of batteries using silicon-based active materials.

[0192] In other words, it has been confirmed that the negative electrode composition according to the present application has a high content of silicon-based active material particles, thereby making it possible to obtain a high-capacity and high-density negative electrode, and also solves problems such as volume expansion caused by having a high content of silicon-based active material particles. [Explanation of symbols]

[0193] 10 Negative electrode current collector layer 20...Negative electrode active material layer 30 Separator 40...Cathode active material layer 50 Positive electrode current collector layer 100 ···Negative electrode for lithium secondary battery 200 ···Positive electrode for lithium secondary batteries

Claims

1. A negative electrode composition comprising a silicon-based active material, a negative electrode conductive material, and a negative electrode binder, The negative electrode binder has a Young's modulus of 10 3 MPa or more, and a second binder having a tensile deformation rate (strain) of 15% or more; The negative electrode binder satisfies the following formula 1: [Formula 1] 1≦X / Y<4 In the above formula 1, Y represents the weight part of the first binder based on 100 parts by weight of the negative electrode binder; X represents the part by weight of the second binder based on 100 parts by weight of the negative electrode binder.

2. The X is 50 parts by weight or more and 95 parts by weight or less based on 100 parts by weight of the negative electrode binder, The negative electrode composition according to claim 1 , wherein Y is 5 parts by weight or more and 50 parts by weight or less based on 100 parts by weight of the negative electrode binder.

3. The negative electrode composition of claim 1 , wherein the negative electrode binder is present in an amount of 1 part by weight to 20 parts by weight based on 100 parts by weight of the negative electrode composition.

4. The first binder comprises one or more selected from the group consisting of PAA, PAN, and PAM; The negative electrode composition of claim 1 , wherein the second binder is a rubber-based binder.

5. The negative electrode composition according to claim 1 , wherein the silicon-based active material is present in an amount of 60 parts by weight or more based on 100 parts by weight of the negative electrode composition.

6. 2. The negative electrode composition according to claim 1, wherein the silicon-based active material comprises one or more selected from the group consisting of SiOx (x=0), SiOx (0<x<2), SiC, and a Si alloy.

7. 2. The negative electrode composition according to claim 1, wherein the silicon-based active material comprises one or more selected from the group consisting of SiOx (x=0) and SiOx (0<x<2), and the silicon-based active material comprises 70 parts by weight or more of the SiOx (x=0) based on 100 parts by weight of the silicon-based active material.

8. The negative electrode composition according to claim 1 , wherein the negative electrode conductive material is present in an amount of 0.1 parts by weight to 40 parts by weight based on 100 parts by weight of the negative electrode composition.

9. The negative electrode composition according to claim 1 , wherein the negative electrode conductive material comprises at least one selected from the group consisting of a dot-like conductive material, a sheet-like conductive material, and a linear conductive material.

10. 10. The negative electrode composition according to claim 9, wherein the negative electrode conductive material comprises 80 parts by weight or more and 99.9 parts by weight or less of the sheet conductive material and 0.1 parts by weight or more and 20 parts by weight or less of the linear conductive material, based on 100 parts by weight of the negative electrode conductive material.

11. The negative electrode composition of claim 1 , wherein the first binder has a weight average molecular weight of 100,000 g / mol to 2,000,000 g / mol.

12. A negative electrode current collector layer, and A negative electrode active material layer comprising the negative electrode composition according to any one of claims 1 to 11, which is formed on one or both sides of the negative electrode current collector layer. A negative electrode for a lithium secondary battery comprising:

13. 13. The negative electrode for a lithium secondary battery according to claim 12, wherein an adhesive strength of a surface of the negative electrode active material layer in contact with the negative electrode current collector layer satisfies 100 gf / 5 mm or more and 500 gf / 5 mm or less under conditions of 25° C. and normal pressure.

14. The thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, 13. The negative electrode for a lithium secondary battery according to claim 12, wherein the negative electrode active material layer has a thickness of 20 μm or more and 500 μm or less.

15. positive electrode, A negative electrode for a lithium secondary battery according to claim 12 . A separator provided between the positive electrode and the negative electrode; and electrolyte, A lithium secondary battery comprising:

Citation Information

Patent Citations

  • Wound type nonaqueous electrolyte secondary battery and its negative electrode

    JP2006339093A

  • Negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery

    JP2013229163A

  • Negative electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2015198038A

  • Anode active material slurry, anode using the slurry, and electrochemical element containing the same

    JP2015535643A

  • Electrode for nonaqueous electrolyte secondary battery

    JP2016219370A